Isolation, cultivation and genomic analysis of magnetosome biomineralization genes of a new genus of South-seeking magnetotactic cocci within the Alphaproteobacteria - Morillo, Viviana; Abreu, Fernanda; Araujo, Ana C.; Almeida, Luiz G.; Prast, Alex E.; Farina, Marcos; Vasconcelos, Ana Tereza R.; Bazylinski, Dennis A.; Lins, Ulysses (Frontiers in Microbiology, 2014)
Although magnetotactic bacteria (MTB) are ubiquitous in aquatic habitats, they are still considered fastidious microorganisms with regard to growth and cultivation with only a relatively low number of axenic cultures available to date. Here, we report the first axenic culture of an MTB isolated in the Southern Hemisphere (Itaipu Lagoon in Rio de Janeiro, Brazil). Cells of this new isolate are coccoid to ovoid in morphology and grow microaerophilically in semi-solid medium containing an oxygen concentration ([O2]) gradient either under chemoorganoheterotrophic or chemolithoautotrophic conditions. Each cell contains a single chain of approximately 10 elongated cuboctahedral magnetite (Fe3O4) magnetosomes. Phylogenetic analysis based on the 16S rRNA gene sequence shows that the coccoid MTB isolated in this study represents a new genus in the Alphaproteobacteria; the name Magnetofaba australis strain IT-1 is proposed. Preliminary genomic data obtained by pyrosequencing shows that Mf. australis strain IT-1 contains a genomic region with genes involved in biomineralization similar to those found in the most closely related magnetotactic cocci Magnetococcus marinus strain MC-1. However, organization of the magnetosome genes differs from Mc. marinus.